Analisis Perjanjian Pembangunan Jembatan Bintan-Dompak Antara PT. Nindya Karya dengan Pemerintah Kepulauan Riau - Rina Shahriyani Shahrullah; Ampuan Situmeang; Any Lindawaty (Journal of Judicial Review, 2017)
Dompak Island to Bintan Island bridge construction is a building construction between the government and the private company which then became a written contract that had been agreed by both parties. However, later in time, what was written in the contract was not obeyed by both parties and caused a legal problem between the Riau Islands Government and PT NindyaKarya. Based on the description above, the researcher wanted to analyze Bintan Island- Dompak Island bridge construction implementation whether it had referred to the legal and proportion principles. The researcher also wanted to know the factors, impacts, and efforts that has been done by both parties. The research method that using empirical/sociological law method is done by examining the written positive law requirements used to guide the Bintan Island- Dompak Island bridge construction implementation agreement, and then examined the positive law implementation on the in concreto legal events. The result showed that Bintan Island-Dompak Island bridge construction implementation agreement had not fully obeyed the legal and proportion principles. In the end, the researcher recommended to continue the project of the bridge with the risk of falling down which could bring a big loss to the country, to make the content of the agreement clear and detail, done by the efficient, affective, and accountable goods procurement which in line with the necessity and target set to give a maximum advantages for the society. The legislations made by the government should not contradict each other because it would cause the society to suffer and the welfare society could be realized.